A Clinical and Molecular Description of a Rare Case of Chromosomal Abnormality (Partial Trisomy 14q11.2-q21.1 and Partial Monosomy 21q11.2-q21.3) - Grigory S. Vasilyev; Tatiana I. Meshcheryakova; Elena N. Lukash; Svetlana S. Zhylina; Ilya V. Kanivets; Alexander N. Petrin (Вопросы современной педиатрии, 2016)
The article presents a detailed clinical and molecular and cytogenetic analysis of the unique case of a rare chromosomal abnormality (duplication of 14q11.2-q21.1 and deletion of 21q11.2-q21.3). This chromosomal abnormality is a result of segregation (2:2) of a balanced chromosomal translocation in the father being the carrier. Clinical manifestations in the sick child include delay in physical, psychomotor and speech development, epilepsy, skeletal abnormalities, cleft palate, and multiple development microanomalies. The chromosomal microarray analysis was applied for a precise cytogenetic diagnosis.